Multi-material design optimization of optical properties of particulate products by discrete dipole approximation and sequential global programming - Nees, Nico; Pflug, Lukas; Mann, Benjamin; Stingl, Michael (Structural and Multidisciplinary Optimization, 2023)
The optimal design of nanoparticles with respect to their optical properties is one of the main foci within nanoparticle technology. In this contribution, we suggest a new design optimization method in the framework of which the discrete dipole approximation (DDA) is used to approximate the solution of Maxwell’s equation in time-harmonic form. In the core of the optimization method, each dipole is repeatedly assigned a material property from a given material catalog until a local minimum for the chosen design objective is obtained. The design updates are computed using a separable model of the optimization objective, which can be solved to global optimality, giving rise to a sequential global optimization (SGP) algorithm. We suggest different types of separable models, among them exact separable models as well as tight approximations of the latter which are numerically tractable. The application of the DDA method in the framework of structural design methods widens the spectrum of numerically tractable layout problems in optical applications as, compared to finite element based approaches, significantly more complex design spaces can be investigated.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Discrete dipole approximation; Material optimization; Sequential global programming; Topology optimization